Civic-Military Schools: constitution/rendering of subjectivities for obedience and servitude - Strieder, Roque (2022)
In this study we intend to reflect, to better understand the call for the return of the military forces of command and obedience, as an educational and human valorization model. We try to understand how subjection practices become acceptable - voluntary servitude style -, reducing the person to the condition of a thing, in a plot that perpetuates the violence and cruelty of, and in the so-called social relations, reinforcing the economic, social and cultural inequalities. We started from the problems: Why does a large part of the Brazilian population believe that military order and discipline are suitable for school-age children and young people? What implications arise from the military formation as a constituent of subjectivity? What alternatives to hope for? For a deeper and unveiling understanding of the contradictions and tensions this formative proposition brings - military civic school - we seek support in theoretical references constructed by authors such as  Foucault, Guattari, Maturana, Varela and others, whose reflective aspects invite debates and engagements of different dynamics. We emphasize that civic-military schools, based on hierarchy, domination, order and obedience aim much more at a captured body than at a person's body constituted by the interactions of living experiences. The formative logics that adhere to command and obedience demand surrender to undisputed truths, that, in an instrumental way, frame and condition the people. We believe that the experience of thinking about, and as subjectivity, from the desecration of devices, from autopoiesis as an educational living, and from the production of discontinuities caused by educators, can contribute to overcoming the logic of command and obedience.